Pengembangan Modul Pembelajaran Berbasis Masalah Menggunakan Nearpod untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Sekolah Dasar - Faiqoh, Kholisotul; Fahmi, Muhammad; Syaifuddin, Syaifuddin; Firdausiyah, Nuri Junanul (Jurnal Gentala Pendidikan Dasar, 2025)
Indonesia ranks low in children's interest in reading, parents as the first educators have a crucial role in fostering interest in reading in children. This study aims to analyze the forms of parental roles and factors that influence the success of parental roles in fostering children's interest in reading. This research uses the Systematic Literature Review (SLR) method. The data analysis technique used is content analysis technique. The data used comes from the GARUDA databases. The results of the article search obtained a total of 7 selected articles after filtering. The results of this study show that the descriptive qualitative approach is widely used in research on children's reading interest, namely as many as 6 articles, while quantitative research is only 1 article. Furthermore, this study shows that there are 5 roles of parents in fostering interest in reading in children, namely parents as educators, organizers, inspirers, facilitators and motivators. Factors that influence the effectiveness of parents' role in fostering children's interest in reading are the use of gadgets, mood, environment, and parents' time availability.